2012
DOI: 10.1007/s10534-012-9521-2
|View full text |Cite
|
Sign up to set email alerts
|

Copper deficiency has minimal impact on ferroportin expression or function

Abstract: Interactions between copper and iron homeostasis have been known since the nineteenth century when anemia in humans was first described due to copper limitation. However, the mechanism remains unknown. Intestinal and liver iron concentrations are usually higher following copper deficiency (CuD). This may be due to impaired function of the multicopper oxidases hephaestin or ceruloplasmin (Cp), respectively. However, iron retention could be due to altered ferroportin (Fpn), the essential iron efflux transporter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Moreover, as FPN has not been shown to export Cu, the decrease in Cu levels may be a secondary effect of lowered intracellular Fe due to increased Fe efflux. Fe-deficiency anaemia has been associated with copper deficiencies, though the mechanism remains unknown 45, 46 . Though future studies are needed to further elucidate FPN’s transport profile in C. elegans , the rescue of the pdr-1 mutant phenotype through FPN overexpression supports our hypothesis that metal dyshomeostasis in the background of pdr-1 loss may be due to alterations in transporter expression.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as FPN has not been shown to export Cu, the decrease in Cu levels may be a secondary effect of lowered intracellular Fe due to increased Fe efflux. Fe-deficiency anaemia has been associated with copper deficiencies, though the mechanism remains unknown 45, 46 . Though future studies are needed to further elucidate FPN’s transport profile in C. elegans , the rescue of the pdr-1 mutant phenotype through FPN overexpression supports our hypothesis that metal dyshomeostasis in the background of pdr-1 loss may be due to alterations in transporter expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our nutritional copper deficiency model (Figures 1, 2, 3), duodenal iron content was not significantly altered relative to the control levels, yet Hif-2α was significantly increased. Indeed a number of studies, across species, have shown that iron retention in the gut, (associated with copper deficiency due to a significant decrease in hephaestin feroxidase activity and thus iron export) is not always observed in copper deficiency [17], [37][39] and this provides evidence that cellular iron levels per se may not be the major determinant of HIF-2α protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…Copper deficiency in mice was shown to increase FPN1 mRNA expression, possibly by a transcriptional mechanism involving HIF2α (71). Another recent study, however, provided contradictory results (90). These authors showed that copper restriction of rats and mice had little effect on FPN1 expression or activity.…”
Section: Iron-copper Interactions In Intestinementioning
confidence: 99%